Rebranding, Repackaging, and Digital Marketing Analysis for Micro, Small, and Medium Business Owners - Haes, Putri Ekaresty; Elizabeth, Elizabeth; Lotte, Luckhy Natalia Anastasye; Abdurohim, Abdurohim; Ariawan, Joko (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The purpose of this research study is to analyze rebranding, repackaging, and digital marketing for micro, small, and medium business owners in Indonesia. This study uses a qualitative method with data collection through interviews and focus group discussions with Indonesian Micro, Small, and Medium Business Owners. The results of the study indicate that rebranding, repackaging, and digital marketing program to improve the capabilities of micro, small, and medium businesses is running well.